2015
DOI: 10.1007/s10479-015-1918-1
|View full text |Cite
|
Sign up to set email alerts
|

Service supply chain coordination with platform effort-induced demand

Abstract: In this study we investigate the effort of a service platform in cooperation with a hotel and its influence on the hotel's decision about the quantity of reserved rooms. We begin with a newsvendor hotel facing two kinds of customers: D-customers and C-customers. The D-customers order rooms from the hotel's front desk while the C-customers book rooms through a service platform, i.e., Ctrip.com. The hotel makes decisions about how many rooms to allot to Ctrip.com to achieve optimal profit. Two newsvendor setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Zhang et al (2013) model a supply chain in which a retailer invests in a preservation technology e¤ort and a manufacturer proposes a cooperative program to improve the economic outcomes of all …rms. In the context of service operations, Zha et al (2015) characterize the case in which …rms share the cost when capacity allocation is ine¢ cient. They show the conditions under which a cooperative program leads to coordination (Zha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2013) model a supply chain in which a retailer invests in a preservation technology e¤ort and a manufacturer proposes a cooperative program to improve the economic outcomes of all …rms. In the context of service operations, Zha et al (2015) characterize the case in which …rms share the cost when capacity allocation is ine¢ cient. They show the conditions under which a cooperative program leads to coordination (Zha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of service operations, Zha et al (2015) characterize the case in which …rms share the cost when capacity allocation is ine¢ cient. They show the conditions under which a cooperative program leads to coordination (Zha et al, 2015). Cho and Gerchak (2005) compare traditional coordination schemes such as wholesale price and a revenue-sharing contract to a cooperative advertising program based on operating costs.…”
Section: Introductionmentioning
confidence: 99%
“…Using network and new information technologies, e-platforms create an internet-based mode of contact between the manufacturer and its consumers, opening up an extensive customer base, enormous purchasing information and databases (Zha et al 2015). A recent study has shown the possibility of using Twitter data for supply chain research (Chae 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Service intermediation platforms do not have a hardware-software structure. Several studies have focused on service intermediation platforms, such as online travel agents [74], hotel reservation services [75], taxi-hiring services [76], and grocery-delivery services in the sharing economy [77]. These platforms usually act as an intermediary between existing services rather than develop new services.…”
Section: Limitations and Future Researchmentioning
confidence: 99%